INITIAL RESULT OF IN VITRO FERTILIZA AT HUNG YEN HOSPITAL OF OBSTETRICS AND PEDIATRICS (Vietnam Journal of Community Medicine, 2022)
Research 75 casese of in vitro fertilitiza were first performed at ObGYN and Pediatrict HungYen Hospital.Objective: Indications of IVF and evaluate initial results of IVF cases. Method: discribtiveretrospective.Results and discussion: Fertilization rate was 81,05 ± 23,01%, the average number offertilizatedoocyte was 8,3 ±4,8; The average number of embyros was 6,7 ± 4,7; The rate ofEmbryos transferred was 25,4%, The rate of Embryos Frozen transferred was 74,6 %, Pregnancyrate was 48,7%, Clinical pregnancy rate was 36,9%, 25 babies was born.
Keywords: Invitro fertilization